Strength Analysis and Structure Optimization of the Crankshaft of an Opposed-Power Reciprocating Pump - Chuan Liu; Xiuting Wei; Zuyao Yi; Zhiqin Li; Changhao Zhu; Ze Ma (Machines, 2023)
The opposed-power reciprocating pump has the characteristics of high pressure, large flow, and high efficiency and energy saving. However, due to the special structure of the opposed-power reciprocating pump, existing theoretical methods cannot analyze its dynamic performance. Therefore, this paper proposes a method of analyzing the power end of the opposed-power reciprocating pump. Firstly, according to the working principle and structural characteristics of the traditional plunger pump, the novel and complex structure of the opposed-power reciprocating pump is analyzed by analogy, and the force analysis model of the crankshaft is established. The dynamic analysis model of the Matlab program is used to solve the dynamic load and section stress in the working process, and the variation law of crankshaft load is obtained. The 25 most critical working conditions are selected for analysis, and the most critical station and section of the crankshaft are obtained. With the connection between ANSYS Workbench and Solidworks, the model is imported into ANSYS Workbench, the load on the crank pin is loaded by APDL command flow, and the static analysis of the crankshaft is carried out to obtain the stress and strain of the crankshaft. Finally, the static and fatigue strength of the dangerous section is checked, and it is proven that the strength and stiffness of the crankshaft meet the design requirements. The results show that the dynamic analysis results of the crankshaft under critical working conditions are consistent with the finite element analysis, verifying the rationality of the method and providing a reference for the improvement and optimized design of the crankshaft of the opposed-power reciprocating pump.